Pirates of the Caribbean. Dead man's chest [videorecording (Blu-ray + DVD)] - Verbinski, Gore; Depp, Johnny; Bloom, Orlando, 1977-; Knightley, Keira, 1985-; Davenport, Jack, 1973-; Nighy, Bill, 1949-; Wolski, Dariusz A.; Zimmer, Hans; Elliott, Ted, 1961-; Rossio, Terry; Beattie, Stuart; Wolpert, Jay (Disney DVD, 2011)
Captain Jack owes a blood debt to the legendary Davy Jones, who captains the ghostly Flying Dutchman. Unless Jack can find a way out, he will be cursed to an afterlife of eternal servitude and damnation.